Decentralized Administration and Minority Accommodation in Sri Lanka: Analyzing Status, Issues, Challenges and Prospects - Yusoff, Moharnrnad Agus; Sarjoon, Athambawa; Asrinaldi, Asrinaldi; Mohd. Zain, Zawiyah (MCSER Publishing, Rome-Italy, 2015)
One of the major objectives of decentralization is to facilitate the administrative machinery of a government to deliver public services efficiently and effectively to all segment of public, including the minority groups living within a state. In a multi-ethnic country, the decentralized administration with specific provisions and institutional arrangements can help to promote and protect the rights and privileges of minorities. However, in Sri Lanka, decentralization has been a contested topic of debate in terms of minority accommodation. This study attempts to access the constitutional and institutional arrangement of ethnic minority accommodation in decentralized administration, the status of their practice, and the related issues in Sri Lanka. The finding reveals that even though Sri Lanka has adopted decentralized administrative system at different levels, but it has failed to accommodate the rights and interests of ethno-linguistic minorities within the system. The study identifies the non-implementation of the constitutional provisions on minority language (Tamil) in administrative affairs as one of the key factors motivated to the minority grievances in decentralized administration in Sri Lanka. It is further identified that the lack of commitment to follow and implement the constitutional provisions and the acts of ethnic discrimination and marginalization in administrative affairs have compelled the minorities to claim and advocate for more institutional and policy reforms in decentralization discourse in Sri Lanka